The Impacts of Covid-19 on Racial Inequality in Business Earnings - Robert Fairlie (Center for Economic Studies and ifo Institute (CESifo), 2023)
Many small businesses closed in the pandemic, but were economic losses disproportionately felt by businesses owned by people of color? This paper provides the first study of the impacts of COVID-19 on racial inequality in business earnings. Pandemic-induced losses to business earnings in 2020 were 16-19 percent for all business owners. Racial inequality increased in the pandemic: Black business owners experienced larger negative impacts on business earnings of 12-14 percent relative to white business owners. Regression estimates for Latinx and Asian business owners reveal negative point estimates but the estimates are not statistically significant. Using Blinder-Oaxaca decompositions and a new pandemic-focused decomposition technique, I find that the industry concentrations of Black, Latinx, and Asian business owners placed each of these groups at a higher risk of experiencing disproportionate business earnings losses in the pandemic. Higher education levels among Asian business owners helped insulate them from larger losses from COVID-19. In the following year of economic recovery, 2021, business earnings rebounded strongly for all groups except for Asian business owners who experienced large relative losses (which were partly due to industry concentrations). State-level variation in policies and disease spread does not explain racial differences in business earnings losses or rebounds.
Keywords: L26; J15; 330; entrepreneurship; Covid; racial inequality; business earnings; pandemic